Job Satisfaction And Performance Analysis of BTM Employees In Central Java - Galih Prakoso; Suryo Budi Santoso; Naelati Tubastuvi; Sri Wahyuni (Jurnal Ilmiah Ekonomi Islam, 2023)
The aim of this study is to analyze the Islamic work ethics, motivation, compensation effect both direct and indirectly through job satisfaction to performance. The relationship between variables using the concepts in the theory of social change and Maslow's perception of basic human needs. This is quantitative research with primary data obtained from questionnaires filled out by BMT employees throughout Central Java with as many as 185 research samples. The research data were analyzed for the level of validity and reliability and then processed using the Structural Equation Model (SEM). The findings show that Islamic work ethic, motivation and compensation positively affect employee performance both direct and indirect through job satisfaction as an intervening variable. The results of this study confirm the theory of social change and Maslow's theory that socially valued activities within a company can positively increase employee performance. This research has implications for microfinance institutions to be able to implement effective strategies to improve internal performance. This research is limited to microfinance which is directly intervened by the Muhammadiyah Foundation